IDEAL framework for surgical innovation 1: the idea and development stages - McCulloch, Peter; Cook, Jonathan A.; Altman, Douglas G.; Heneghan, Carl; Diener, Markus K. (The BMJ, 2013)
IDEAL is a framework for evaluations of surgical innovations, which follow a distinct development pathway differing from the approach developed for pharmacological interventions. Many pathway and evaluation challenges are shared by other interventional therapies, requiring individual therapist skills and customisation of treatment to the individual, partly through medical devices. This paper provides an overview of the IDEAL framework and recommendations, and focuses on the first two stages: idea and development.
Gesehen am 08.07.2021